2019
DOI: 10.3390/en12040761
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study and Mechanism Analysis of the Effect of Oil Viscosity and Asphaltene on Foamy Oil

Abstract: Foamy oil is considered an important reason for the anomalous performance in depletion development for some heavy oil reservoirs, but its influence factors remain to be fully investigated. In order to determine the effect of oil viscosity and asphaltene on foamy oil, ten oil samples including two types (deasphalted oil and asphaltenic oil) and five viscosities were used in the work. On this basis, depletion experiments were conducted in a sandpack and microscopic visualization model. Then, viscoelastic moduli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Although the diluting method would change the content of four components in oil and then affect the foamy oil formation and performance to a certain extent, this effect is small compared with the influence of oil viscosity. On the one hand, we know from our previous study that oil viscosity is the dominant factor affecting foamy oil, the effect of which is much larger than that of asphaltenes, and on the other hand, we can see from Table that the content change of four components in oil caused by the naphtha addition was relatively little. Therefore, the difference in foamy oil performance can be attributed mainly to the change of oil viscosity.…”
Section: Methodsmentioning
confidence: 79%
“…Although the diluting method would change the content of four components in oil and then affect the foamy oil formation and performance to a certain extent, this effect is small compared with the influence of oil viscosity. On the one hand, we know from our previous study that oil viscosity is the dominant factor affecting foamy oil, the effect of which is much larger than that of asphaltenes, and on the other hand, we can see from Table that the content change of four components in oil caused by the naphtha addition was relatively little. Therefore, the difference in foamy oil performance can be attributed mainly to the change of oil viscosity.…”
Section: Methodsmentioning
confidence: 79%
“…The results manifested that the bubble size in the foams makes a difference with the viscosity and surface tension. Foamy oil was studied by Wang et al, 17 who looked into the role of asphaltenes and oil viscosity. The results reveal that as the oil viscosity increases, the interfacial viscous modulus also rises dramatically, which means the interfacial film becomes more robust and rigid.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the sandbag model was most commonly used to test the Huff-n-Puff process. ,, Ahadi used a sandbag model with a porosity of 32.3% to investigate the recovery capacity of CH 4 /C 3 H 8 mixed solvents in the CSI process. The results showed that there was an optimal ratio when C 3 H 8 was added to CH 4 , and the ultimate recovery factor did not increase significantly after the concentration was exceeded.…”
Section: Introductionmentioning
confidence: 99%